Tax Management of Related Parties: A Literature Review on Transfer Pricing Practices and Regulations in Indonesia - Fajriyati, Sausan; Nurfalah, Sunita; Pahala, Indra; Wahono, Puji (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Transfer pricing practices have become a central focus in international taxation as a common tax planning strategy employed by multinational corporations. In Indonesia, regulations related to transfer pricing have undergone significant developments in an effort to align with international standards. Through a comprehensive analysis of recent literature, this article examines tax management concerning related party transactions, focusing on three main aspects: the concept of related parties in taxation, tax regulations on intercompany transactions, and fair price determination mechanisms. The main findings indicate that although Indonesia's transfer pricing regulations have adopted OECD standards, their implementation still faces challenges such as limited comparable data and the complexity of related party transactions. This article also identifies effective strategies in tax management for related parties, including the application of Advance Pricing Agreements (APA) and comprehensive transfer pricing documentation.